2020
DOI: 10.1080/17538157.2020.1834399
|View full text |Cite
|
Sign up to set email alerts
|

Can caregivers trust information technology in the care of their patients? A systematic review

Abstract: The Health Insurance Portability and Accountability Act of 1996 (HIPAA) requires that healthcare providers allow patients to engage in their healthcare by allowing access to their health records. Often patients need informal caregivers including family members or others to help them with their care. This paper explores whether trust is a key factor for informal caregivers' decision to use health information technologies (HIT) including electronic health records (EHR), patient portals, mobile apps, or other dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Here, five potential topics are generated by topic analysis. Topic 1 (3170 studies) consists of subject-related studies, and various researches 39,40 presented lots of subjects such as patient, child, and family in nursing informatics. For the hospital-based research group (topic 2, 2555 studies), many studies focused on medical costs or medication errors 41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, five potential topics are generated by topic analysis. Topic 1 (3170 studies) consists of subject-related studies, and various researches 39,40 presented lots of subjects such as patient, child, and family in nursing informatics. For the hospital-based research group (topic 2, 2555 studies), many studies focused on medical costs or medication errors 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, five potential topics are generated by topic analysis. Topic 1 (3170 studies) consists of subjectrelated studies, and various researches 39,40 presented lots of…”
Section: Discussionmentioning
confidence: 99%
“…Eight reviews directly examined relationships and/or trust in the context of eHealth. 59,67,68,69,70,71,72,73 Eleven reviews examined related concepts like communication, interaction, and therapeutic alliance in an eHealth context. 61,62,74,75,76,77,78, 79,80,81,82 In all other reviews, relationships and/or trust were not the focus but were discussed along with other ndings.…”
Section: Overview Of Reviewsmentioning
confidence: 99%
“…Eight reviews directly examined relationships and/ or trust in the context of eHealth [59,[79][80][81][82][83][84][85]. Eleven reviews examined related concepts like communication, interaction, and therapeutic alliance in an eHealth context [61,62,[86][87][88][89][90][91][92][93][94].…”
Section: Fig 2 Number Of Reviews By Yearmentioning
confidence: 99%
“…Forty-seven reviews reported a mix of positive and negative impacts of eHealth on patient-provider relationships [16, 54, 57, 59, 62, 64-68, 70, 72, 74, 73, 75, 76, 78-81, 85, 88, 89, 91, 92, 95-99, 104-108, 112, 113, 116, 117, 120, 122-124, 126-129] (e.g., communicating via technology created a distance between the patient and provider in some instances, but also reduced loneliness in others). Nineteen reviews reported mainly positive impacts (e.g., more collaboration and closeness between patient and provider) [53, 55, 56, 60, 71, 77, 83, 100, 102, 103, 109-111, 115, 118, 119, 121, 125, 130] while seven reviews reported mainly negative impacts (e.g., reduced conversation flow) [58,61,63,69,82,87,114]. Three reviews noted no impact of technology on patientprovider relationships [84,93,94].…”
Section: Impact Of Ehealth On Patient-provider Relationshipsmentioning
confidence: 99%